Detecção de Xanthomonas campestris pv. campestris em sementes de canola tratadas e variabilidade genética de uma coleção de isolados - Diniz, Rayane Louise Candida (2021)
Canola (Brassica napus L. var. oleifera) is an oilseed developed in Canada from the genetic improvement of rapeseed plants, which can be used in the production of edible oil and biodiesel. Black rot caused by the bacterium Xanthomonas campestris pv. campestris (Xcc) is one of the most destructive diseases in canola, occasioning losses in production and productivity. The bacteria can survive in the seeds and the use of healthy seeds is recommended in the management of disease. The objectives of this study were to evaluate and to compare the efficiency of semi-selective culture media for the detection of Xcc; to detect the presence of the bacteria in seed-treated canolas and to culturally, biochemically and molecularly characterize 34 isolates of Xcc from various brassicas including cultivars of B. oleracea and B. napus. For evaluation of the culture media an Xcc. isolate was used in four media 523, NA, NSCAA and YDC, with and without cycloheximide fungicide with three replications in each; the efficiency of each medium was assessed from the diameter of the colonies and counting the number of colonies in CFU mL-1. The 34 Xcc isolates were characterized biochemically, physiologically and molecularly, using specific primers XCF/XCR and universal (BOX, ERIC). The 523, NA and NSCAA culture media with the addition of cyclohexamide were efficient for the detection of the bacteria in the seed extract. The isolates were culturally, biochemically and molecularly characterized and 33 were identified as Xcc. The isolates showed genetic variability by BOX and ERIC-PCR, and it was not possible to group them according to geographic region and or host of origin.